Donkey work: redefining the Democratic Party in an 'age of conservatism,' 1972-1984 - Andelic, P; Davies, G (2015)
This thesis argues that much of the political historiography is mistaken in portraying the post-1960s United States as a nation moving inexorably to the right. It also argues that historians should not understand the Democratic Party as being in terminal decline between 1972 and 1984, marginalised by a coalescing conservative Republican majority. Indeed, taking as its focus the U.S. Congress, this thesis asks why the remarkable resilience of the congressional Democratic Party has been overlooked by historians. It further asks why that resilience did so little to help the party in subsequent years. The Democratic revival in the elections of 1974 and 1976, so often dismissed as a post-Watergate aberration, was in fact an authentic political opportunity that the party failed to exploit. Exploring various Democratic factions within Congress that competed to shape their party's public philosophy, this thesis seeks to show how grander liberal ambitions were often subordinated to the logic of legislative politics and policymaking. The underlying theme is the unsuitability of Congress as an arena for the discussion and refinement of post-Great Society liberalism. Again and again, the legislature displayed a remarkable facility for undermining iconoclasm and stalling policy experimentation. Institutional reforms in the early 1970s, supposed to reinvigorate the Congress and the congressional Democratic Party, actually succeeded only in intensifying the fragmentation of both. Congressional politics became more entrepreneurial and less party-oriented, leaving legislators with few incentives to look beyond their own political fortunes to the party’s future prospects. Enduring Democratic strength in Congress meant that Capitol Hill remained at the centre of the party's efforts to reclaim its preeminent position in American politics. The fact that the Democrats never experienced a protracted period of minority status, as the Republicans did during much of the mid-twentieth century, left them ill-equipped and without a powerful incentive to think in broader terms about their party’s mission.